EFEITO ANTITUMORAL DE DUAS GUANIL-HIDRAZONAS EM LINHAGENS DE CÂNCER DE MAMA HUMANO - TEIXEIRA, Danrley Moraes (2024)
Cancer currently represents one of the main public health problems in the world, becoming a limiting factor in life expectancy. In this context, the search for new drugs with antitumor activity gains importance. Hydrazones and guanylhydrazones are organic compounds with several biological activities already observed, including antineoplastic activity. Thus, the objective of this study was to evaluate the antitumor activity of two guanylhydrazones, guanylhydrazone from 5,7-dibromo-3,3-dimethyl-3,4-idroacridin- 1-(2H)-one (D9) and guanylhydrazone from phenanthrenequinone (D10), in human breast cancer cell lines. For this purpose, cell viability, clonogenic, slit migration, cell cycle and cell death assays were performed in the human breast cancer cell lines, MCF-7 and MDA-MB-231. In the cell viability assay, compounds D9 and D10 showed a concentration-dependent reduction in viability in both cell lines. In the clonogenic assay, D9 and D10 demonstrated significant loss in colony formation capacity, especially D9 at all concentrations, in both cell lines. In migration, both guanylhydrazones showed anti-migratory activity in both cell lines, especially at the highest concentrations of 50 and 100 μM, with compound D9 standing out. In the cell cycle evaluation, it was observed that D9 and D10 did not cause significant changes in the phases of the tumor cell cycle, except for the MDA-MB-231 cell line, which showed a higher frequency of cells in the G2 phase. Finally, in the results of the cell death assay, it was noted that D9 reduced cell viability and increased the frequency of apoptotic cells in MCF-7 at all concentrations, while D10 produced the same only at the highest concentration. In MDA-MB-231, both compounds promoted a reduction in viability and an increase in the frequency of apoptotic cells at all concentrations. From these results, we can conclude that both guanylhydrazones D9 and D10 have antitumor activity, with emphasis on cytotoxic, antiproliferative, anti-migratory and pro- apoptotic activity in female breast cancer cells.